The effect of Professional Nursing Practice Model Training (MPKP) with the implementation of Pillar IV Nursing Care Delivery System (Pillar IV NCDs) at a Hospital in Kotamobagu, Indonesia - Tri Ismu Pujiyanto; Helkim Sarino Laode Manika; Rita Dewi (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2023)
Background: Professional Nursing Practice Model Training (Model Praktik Keperawatan Profesional; MPKP) is one of the efforts to improve the quality of service in hospitals in nursing services to minimize errors or omissions that can occur. The training carried out is expected to be able to improve the implementation of pillar IV NCDS in hospitals. Aims: This study aimed to determine the effect of MPKP training with the application of pillar IV NCDS at the General Hospital of the Evangelical Masehi Church Bolaang Mongondow Monompia Kotamobagu. Methods: This research is a quantitative research type with a pre-experimental research design one group pre-test post-test design. This research was conducted in August 2022 as many as 52 nurse respondents working at the Monompia GMIBM Hospital Kotamobagu. Results: From the survey, it shows that the intervention will increase the number of nurses implementing the Pillar IV Nursing Care Delivery System (Pillar IV NCDs) including the assessment element (from 76.9% to 90.4%), nursing diagnosis (from 36.5% to 75.0%), planning (from 51.9% to 88.5%), action or measurement (from 84.6% and 92.3%), evaluation (from 46.2% to 90.4%), and nursing care notes (78.8% and 98.1%). There are differences in the implementation of pillar IV NCDS before and after being given MPKP training (p-value: <0.001). it is known that education level and the work experience of the nurses will significantly determine the success of the training, respectively with p value of <0.001 and 0.004. Conclusion: From the survey, we may note how the Professional Nursing Practice Model Training (MPKP) affecting the number of nursing implementing the Pillar IV NCDs. Data from the results can be used as recommendation to the hospitals' human resources department in designing their program in order to increase the nurses' competences.